Dynamics and determinants of right-wing populist mobilisation in Germany - Sebastian Hellmeier; Johannes Vüllers (West European Politics, 2022)
Western Europe has recently experienced increasing protest mobilisation by right-wing populist movements. Although these movements are receiving increasing scholarly attention, systematic data on protest activities is limited. In this research note, original data is used to describe the protest activity of Germany's Pegida movement across space and time and to explore the city-level determinants of protest mobilisation. The protest dataset records 373 events with more than 337,000 participants in major cities between 2014 and 2017. The data documents the involvement of right extremists during the protests and illustrates the movement's nativist and anti-elitist orientation. The correlational analysis of the determinants of protest activity shows that protests are less likely in cities with a large foreign-born population and lower income levels. Moreover, protests correlate with vote shares for the right-wing populist party AfD, underlining the party-movement linkage and the local entrenchment of right-wing ideology.
Keywords: 330; right-wing populism; far right; protest; mobilisation; Pegida